Opposite Effects of Insulin on Focal Adhesion Proteins in 3T3-L1 Adipocytes and in Cells Overexpressing the Insulin Receptor - Wang, Qinghua (The American Society for Cell Biology, 1998)
Insulin can regulate the abundance and organization of filamentous actin within cells in culture. Early studies using cell lines that overexpress the insulin receptor demonstrated that insulin caused a rapid reversible disassembly of actin filaments that coincided with the rapid tyrosine dephosphorylation of focal adhesion kinase. We have extended these studies by demonstrating that paxillin, another focal adhesion protein, and Src undergo tyrosine dephosphorylation in response to insulin in Chinese hamster ovary (CHO) and rat hepatoma (HTC) cells that overexpress the insulin receptor. This contrasted with the effect of insulin in parental CHO and HTC cells in which focal adhesion proteins were not dephosphorylated in response to the hormone. In addition, insulin caused a dispersion of focal adhesion proteins and disruption of actin filament bundles only in cells that overexpressed the insulin receptor. Moreover, in 3T3-L1 adipocytes, which are considered prototypic insulin-responsive cells, actin filament assembly was stimulated, and focal adhesion protein tyrosine phosphorylation was not altered. 3T3-L1 cells have more insulin receptors than either parental CHO or HTC cells but have fivefold less insulin receptors than the overexpressing cell lines. We hypothesize that a threshold may exist in which the overexpression of insulin receptors determines how insulin signaling pathways regulate the actin cytoskeleton.